Koping keluarga terhadap anggota keluarga yang mengalami ketergantungan narkoba diwilayah kota Semarang - Iswanti, Dwi Indah; Suhartini, Suhartini; Supriyadi, Supriyadi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2007)
Drugs addicted is condition which is conceptualized as a mental illness, that consider about mental and behavior disorders caused drugs abuse. Family’s coping to family member drugs addicted, talked about various coping which used by family within face so many problems that emerge caused by drugs addicted.The problem formulation was how family’s coping to face family member drugs addicted?The research aims were to know about sign and phenomenon drugs addicted, family response towards family member drugs addicted, to know kind of coping and identified coping strategies that used whether internal or external. Approach research method used qualitative design with phenomenology. Research instrument used in depth interview.The results were signs and phenomenon drugs addicted who had different, family responses: feel confused, worry, sad, guilty, disappointed and embarrassed to community. Whereas, family’s coping used constructive coping with activate coping strategies whether internal or external.Conclusion: The family used coping mechanism being effective to face family member drugs addicted.